POSSIBILITIES OF ENSURING WARP YARN TENSION IN THE WEAVING PROCESS (Multidisciplinary Journal of Science and Technology, 2025)
In this scientific article, the research results aimed at analyzing the physico-mechanical properties of Nm-34/1 yarns, which play an important role in the textile industry, as well as the tension levels of warp yarns during the weaving process, are presented. During the study, the breaking force, elongation, extensibility, and work at break of the yarns were determined under laboratory conditions, and their impact on the production process was comprehensively examined. At the same time, the fact that the coefficients of variation (CV%) ranged between 6–15% proved the existence of a certain degree of unevenness in the physico-mechanical properties of the yarns.In general, the conducted studies show that an in-depth analysis of the physico-mechanical properties of Nm-34/1 yarns and the development of technological solutions for stabilizing warp yarn tension have significant practical importance in increasing production efficiency, reducing waste, and improving the quality of the finished fabric.